Gavin Families. A Report Paul Neufeld Weaver and Others. - Weaver, Paul Neufeld (Distributed by ERIC Clearinghouse, 1991)
The Family Literacy Project at the Dr. Charles E. Gavin School in Chicago Heights, Illinois, brings together a community college adult education program, an early childhood program, and a local school district. This report of the Prairie State College Family Literacy Project assesses the needs for family literacy among the families in the Gavin School neighborhood. Goals were to document the nature of the community, determine the interests and perceived needs of adult family members, empower the community members, and raise awareness in the community of the program and recruit participants. Emphasis was on data collection and this report reflects that focus. The majority of families in the area were found to be African American and Hispanic, to have high rates of high school dropout parents and teenage mothers, to have lived in the area an average of 12 years, and to have relatively low levels of parent involvement in the schools. Parents and teachers differed on types of activities perceived to be needed for parents, with teachers ranking the need for parenting skills highest. Additional demographic data are reported and the survey form and responses are appended. (Adjunct ERIC Clearinghouse on Literacy Education) (LB)